Junior High School Students' Skills in Making Posters through the Blended Learning Model - Ismawati; Jati, Sigit Pramono; Khoiril (ICONELT, 2024)
In the Indonesian context, writing is considered a painful activity, indicating that oral culture is much better than writing. The students' works are sufficiently kept in the libraries, although publishing those is much more worthwhile. Therefore, it is necessary to improve the student's writing skills. This research aims to investigate the skills of junior high school students in Surabaya in making posters using the blended learning model with qualitative research methods. The study focuses on enhancing students' abilities to create effective and impactful posters. The findings indicate that the blended learning model plays a significant role in improving students' poster-making skills. Students develop essential skills in creating informative and visually appealing posters by integrating character education and literacy programs into the learning process. The research showed that students' abilities were highest in design (36℅), then content and massage (32%). The high frequency of designing shows that students are proficient in increasing creativity using Canva. However, challenges such as content clarity and language use require further improved teaching.